Peran Mahasiswa Kampus Mengajar 6 Dalam Meningkatkan Kemampuan Literasi Peserta Didik Di SD Negeri Tangkisan, Kecamatan Bayan, Kabupaten Purworejo - Widiyohening, Caecilia Rosma; Supriono, Supriono; Ayuningtyas, Pratika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Education in Indonesia provides the widest opportunities for students to develop themselves. With the Independent Learning Curriculum, students are encouraged to be more creative and innovative. One of the flagship programs of the independent learning curriculum is the Teaching Campus. The teaching campus program is part of the independent campus program, which has made an important contribution to the progress of education in Indonesia. Students from the teaching campus will be placed in various assignment schools, with the main target of this program being elementary schools (SD) and junior high schools located in the region. 4T (Frontier, Outermost, Disadvantaged, and Transmigration Zones), as well as schools with accreditation below A. The aim of this service is to improve the literacy skills of students at SD Negeri Tangkisan, Bayan sub-district, Purworejo Regency. The partner involved is SD Negeri Tangkisan. This service is carried out in three stages: preparation by attending debriefing and observing placement schools; and implementation of the Teaching Campus program. The approach used in this research is a qualitative approach with descriptive methods. In data collection techniques, the author uses documentation techniques for each activity carried out and then reviews them in several bibliographies. The results of the service show that there are changes and good impacts for students, teachers, and schools, such as increasing the quality of students' reading skills, facilitating reading rooms, providing assistance to the School Literacy Movement, and assisting in adapting technology and administration in the school library. The school feels helped by these activities. Students also feel happy, enthusiastic, and motivated to come to the library, visit the reading corner during breaks, and are active in the school literacy movement.